Determination of Investment Project Management as a Method of Scientific and Technical Progress in the Engineering Industry - et. al, Vladimír Modrák (International Journal of Advanced Science and Technology, 2020)
Investment management is one of the important tasks of the company's policy. Such management depends on the level of innovation potential of the company on the ability to adopt economic and organizational solutions that ensure the achievement of the set objectives and maintain the competitiveness of enterprises. Implementing the innovation investment management system in the engineering industry is of paramount importance and requires the creation of the infrastructure needed to intensify the innovation investment process. This article is focused on the determination of investment project management serving as a means of scientific and technical progress in the engineering industry. The introduction of the article highlights the importance of this issue at the global level and subsequently determines the investment project within the engineering company. The main part of the article provides a description of the management of investment projects in the engineering industry on the basis of which in the final part is drawn a general conclusion on this issue.